Managing the Intravenous Calcium Shortage: Evaluation of Calcium Chloride Stability in 0.9% Sodium Chloride and Dextrose 5% Water Polyvinyl Chloride Bags - Kiser, Tyree H. (Hosp Pharm, 2012)
BACKGROUND: Intravenous calcium chloride (CaCl) is commonly used by inpatient practitioners for a myriad of indications from electrolyte abnormalities to advanced cardiac life support. Currently, a paucity of data is available regarding the stability of CaCl after preparation of intravenous admixtures. PURPOSE: This study evaluated the physical and chemical stability of CaCl 10% diluted in 0.9% sodium chloride or dextrose 5% water polyvinyl chloride bags. METHOD: CaCl 10% solution (1000 mg) was diluted with 0.9% sodium chloride or dextrose 5% water 100 mL for injection to a final concentration of 10 mg/mL. CaCl 10% solution (2000 mg) was diluted with 0.9% sodium chloride or dextrose 5% water 150 mL for injection to a final concentration of 13.3 mg/mL. Each of the preparations were stored at room temperature (23-25°C) and exposed to fluorescent light. Samples of each preparation were analyzed on days 0, 2, 3, 5, and 7. Sterility and physical stability were assessed. Chemical stability of CaCl was evaluated by indirect potentiometry. RESULTS: CaCl 10 mg/mL and 13.3 mg/mL solutions in polyvinyl chloride bags were physically stable during the entire 7-day study period. CaCl retained >90% of the original concentration at 7 days after preparation in 0.9% sodium chloride and dextrose 5% water. CONCLUSION: CaCl diluted to 10 mg/mL or 13.3 mg/mL with 0.9% sodium chloride or dextrose 5% water for injection is both physically and chemically stable for a period of 7 days with ≤10% degradation under conditions of room temperature with fluorescent lighting.